IMPROVEMENT OF CRITICAL THINKING ABILITY THROUGH COOPERATIVE LEARNING MODEL TYPE GROUP INVESTIGATION IN EYES OF SOCIAL SCIENCES IN STUDENT CLASSIC V - Indani Damayanti Damayanti (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
This study aims to improve students' critical thinking skills in social science subjects in grade V SDN Majalengka Kulon I through cooperative learning model of group investigation type. This research uses action research method using Kemmis and Mc.Taggart model consisting of four stages namely, planning, action, observation and reflection conducted for two cycles. Data collection techniques used field notes, documentation, teacher activity observation and student activity observation, test and non test. The subjects in this study are the students of grade V SDN Majalengka Kulon I. The results showed an increase in critical thinking skills. This is evidenced by the average percentage of students in the action cycle I is 69.9%. Teacher activity according to the steps of this method reaches 67,5% and student activity reach 65%. The increase in the second cycle reached 88% of teacher activity in accordance with the steps of this method reached 90% and student activity reached 87.5%. The implication of this research is cooperative learning model of group investigation type to improve critical thinking ability. In the 5th theme teaching subjects are proud as Indonesia. The results of this study indicate an increase in students' critical thinking skills through cooperative learning model type investigation.